MENGEMBANGKAN KETERAMPILAN ABAD KE-21 DALAM PEMBELAJARAN KIMIA - Redhana, I Wayan (Universitas Negeri Semarang, 2019)
In this 21st century, the world is undergoing rapid changes. This change concerns all aspects of life, namely the fields of economics, transportation, technology, communication, information, and others. This change needs to be anticipated by mastering the 21st century skills. The 21st century skills include critical thinking and problem solving, creativity and innovation, communication, and collaboration. The development of the 21st century skills can be carried out in all disciplines. Chemistry as one of the science disciplines is very appropriate to develop the 21st century skills. The development of the 21st century skills must be done intentionally by chemistry teachers in order to achieve the learning objectives effectively and efficiently. To develop the 21st century skills in chemistry learning, the teachers can choose learning models with scientific approaches, such as discovery learning model, problem-based learning model, project-based learning model, or design-based learning. The application of the learning model must be carried out optimally in accordance with the nature of the scientific approach so that students can develop the 21st century skills. In addition, the apllication of blended learning and an assessment of the 21st century skills is also important.